MODEL WRITING WORKSHOP BERBANTUAN MEME DALAM PEMBELAJARAN MENULIS ARGUMENTASI BAGI SISWA BERLATAR TINGKAT PERBEDAAN SELF-AWARENESS - Nenty Erawati, - (2020)
Penelitian ini dilatarbelakangi masih rendahnya kemampuan siswa dalam menulis karangan argumentasi. Hal tersebut disebabkan kurangnya pengalaman yang menarik ketika pembelajaran menulis di sekolah. Selain itu, pemilihan media pembelajaran sangatlah diperlukan agar siswa tertarik dan termotivasi. Tujuan penelitian ini adalah: (1) menggambarkan profil pembelajaran menulis teks argumentasi di SMAS Alfa Centauri (2) membuktikan perbedaan kemampuan menulis argumentasi siswa self-awareness tinggi yang menggunakan model writing workshop berbantuan meme dengan siswa yang menggunakan model terlangsung (3) membuktikan perbedaan kemampuan menulis argumentasi siswa self-awareness rendah yang menggunakan model writing workshop berbantuan meme dengan siswa yang menggunakan model terlangsung (4) membuktikan perbedaan kemampuan menulis argumentasi siswa self-awareness tinggi dengan self-awareness rendah yang menggunakan model writing workshop berbantuan meme (5) membuktikan perbedaan kemampuan menulis argumentasi siswa self-awareness tinggi dan self-awareness rendah yang menggunakan model terlangsung (6) membuktikan ada tidaknya pengaruh antara model writing workshop berbantuan meme dan self-awareness terhadap kemampuan menulis argumentasi siswa. Metodologi penelitian yang digunakan adalah eksperimen desain faktorial 2 x 2. Data hasil belajar diperoleh melalui kegiatan pretest dan posttest. Anova faktorial 2x2 digunakan untuk menganalisis data dengan menggunakan aplikasi SPSS 16. Hasil penelitian menunjukkan: (1) profil pembelajaran menulis argumentasi di SMAS Alfa Centauri masih dikategorikan rendah karena masih rendahnya minat menulis siswa sehingga hasil pretest menunjukkan rata-rata kemampuan siswa masih di bawah KKM (2) terdapat perbedaan kemampuan menulis argumentasi siswa self-awareness tinggi di kelas eksperimen dan kelas kontrol, rata-rata kemampuan siswa kelas eksperimen yang menggunakan model writing workshop berbantuan meme sebesar 84,88, sedangkan kelas kontrol yang menggunakan model terlangsung sebesar 81,07, (3) terdapat perbedaan kemampuan menulis argumentasi siswa self-awareness rendah di kelas eksperimen dan kelas kontrol, rata-rata kemampuan siswa kelas eksperimen yang menggunakan model writing workshop berbantuan meme sebesar 77,30, sedangkan kelas kontrol yang menggunakan model terlangsung sebesar 68,92, (4) terdapat perbedaan kemampuan menulis argumentasi siswa self-awareness tinggi dan self-awareness rendah di kelas eksperimen yang menggunakan model writing workshop berbantuan meme, rata-rata kemampuan siswa self-awareness tinggi sebesar 84,88 dan self-awareness rendah sebesar 77,30, (5) terdapat perbedaan kemampuan menulis argumentasi siswa self-awareness tinggi dan self-awareness rendah yang menggunakan model pembelajaran terlangsung, rata-rata kemampuan siswa self-awareness tinggi sebesar 81,07 dan self-awareness rendah sebesar 68,92, dan (6) terdapat pengaruh antara model writing workshop berbantuan meme dengan tingkat self-awareness siswa terhadap kemampuan menulis argumentasi dibuktikan dengan perolehan nilai signifikansi sebesar 0,047 < 0,050. Kata kunci: model writing workshop, menulis argumentasi, self-awareness siswa This research was motivated by the low ability of students in writing arguments. This is due to the lack of interesting experiences when they learned to write at school. Besides that, the selection of learning media is necessary to make the students are interested and motivated. The objectives of this study were: (1) to describe the profile of learning to write argumentation text at Alfa Centauri High School, (2) to prove the differences of argumentation text writing ability of the high self-awareness students by using meme-assisted writing workshop model and the direct learning model, (2) to prove the differences of argumentation text writing ability of the low self-awareness students by using meme-assisted writing workshop model and the direct learning model, (4) to prove the difference in the ability to write arguments from high self-awareness students with low self-awareness using meme-assisted writing workshop models (5) to prove the difference of argumentation text writing ability between the students with high self-awareness and low self-awareness by using the direct learning model (6) proves whether there is an influence between the meme-assisted writing workshop model and self-awareness on the students' argumentation text writing ability. The research methodology used was a 2 x 2 factorial design experiment. Data on learning outcomes were obtained through the pre-test and post-test activities. The 2x2 factorial ANOVA was used to analyze the data using the SPSS 16 application. The results showed: (1) the profile of learning to write arguments at Alfa Centauri High School was still categorized as low because of the students' low interest in writing so that the pre-test results showed that the average ability of the students was still below KKM (Minimum Mastery Criteria) (2) there is a difference in the students' ability to write arguments with high self-awareness in the experimental class and the control class, the average ability of the experimental class students who used the meme-assisted writing workshop model is 84.88, while the control class using the direct learning model is 81.07, (3) there is a difference in the students' ability to write arguments with low self-awareness in the experimental class and the control class, the average ability of the experimental class students who used the meme-assisted writing workshop model is 77.30, while the control class using the direct learning model is 68.92, (4) there is a difference in the ability to write the argumentation between the students with high self-awareness and low self-awareness in the experimental class using the meme-assisted writing workshop model, the average ability of students with high self-awareness is 84.88 and low self-awareness is 77.30, (5) there is a difference in the ability to write arguments between the high self-awareness students and the low self-awareness students who used the direct learning model, the average ability of high self-awareness students is 81.07 and low self-awareness is 68.92, and (6) there is an influence between the meme-assisted writing workshop model and the level of students' self-awareness on the ability to write arguments is evidenced by the acquisition of a significance value of 0.047 <0.050. Keywords: writing workshop model, writing arguments, student self-awareness